Analisis Keberlanjutan Ekologis Pantai Blibis Banyuwangi dengan Pendekatan Risk Management - Randhi Nanang Darmawan Darmawan; Jemi Cahya Adi Wijaya; Kanom Kanom (Universitas Pendidikan Ganesha, 2022)
Along with the development of tourism in Banyuwangi Regency, there is a beach that has the potential to be developed, the beach is Blibis Beach which is located in District Blimbingsari. However, the ecological sustainability of Blibis Beach is a problem that must be resolved considering the massive amount of waste accompanied by abrasion that often occurs, management that is still far from expectations and minimal government involvement has caused Blibis Beach to be neglected. The purpose of this study is to examine and analyze the risks that arise in Blibis Beach with a risk management approach. The results of this research study are expected to be used as a reference for further development of Blibis Beach. The method used is descriptive quantitative with a risk management approach as for the stages: risk identification, risk assessment (risk matrix), risk response, and risk control. The results show that there are 9 risks that arise and threaten ecological sustainability, with details of 4 risks from Human Resources and 5 risks from Natural Resources, if classified by level, there are 3 extreme risks, 2 high risks, 2 moderate risks, and 2 risks. low. From all the risks that arise, it is necessary to immediately respond and control risks appropriately and involve all related parties, so that the ecological sustainability of Blibis Beach can be developed into one of the best tourist attractions in Banyuwangi.